GIS APPLICATION TO COMPREHENSIVE PREDICTION OF ENVIRONMENTAL IMPACTS OF AIR POLLUTION IN COASTAL INDUSTRIAL AREAS: CASESTUDY OF MINH DUC - BEN RUNG INDUSTRIAL AREA, THUY NGUYEN DISTRICT, HAI PHONG CITY - Lan, Tran Dinh; Ve, Nguyen Dac (Vietnam Journal of Marine Science and Technology, 2009)
GIS technology was applied to assessment and comprehensive prediction of environmental  impacts  of  air  pollution  in  Minh Duc-  Ben  Rung  as  an  example  for  the potentials  of  this  technology in  study  on  environmental  assessment  and  prediction, particularly  on  environment  impact  assessment  and  strategic environment  assessment. Information  layers  of  the  study  area  on  air  quality  (resulted  from  ISC3  conputer  model), landcover/landuse and socio-economic infrastructure stored in GIS database were overlayed to make assessment and comprehensive prediction of the environment and local community health. Study outcomes show the risks of air pollution and local community health due to air pollution were high in Minh Duc County then followed by Tam Hung – Lap Le communes of Hai Phong City.